Making the Man of Law in Dualist Hungary: Alexa David’s Career Strategies and Personal Networks on the Eve of the Twentieth Century - IUDEAN, Ovidiu Emil (Studia Universitatis Babeș-Bolyai Historia, 2018)
The present study focuses on the educational and professional pathway of Alexa David, one of the law graduates hailing from the land of Năsăud/Naszód, in the final decade of the nineteenth and the first part of the twentieth century. David’s experiences exemplify one of the area’s nation-building strategies aimed at establishing a body of individuals trained in law, who could defend the interests of the Romanian nation in Hungarian courts, and contribute to its betterment in all domains. At the same time, because of his kinship ties to the uppermost political echelon in Dualist Hungary, through his uncle Ion Ciocan, a parliamentary representative in Budapest, the Romanian man of law saw himself in a privileged financial position, and was introduced into a wide-ranging network spanning many counties and social-professional levels. He made use of this network in his personal efforts of advancement, and then gave back when he had managed to establish himself as part of the administrative system of the Hungarian, and later on, Romanian state. Rezumat: Formarea juristului în Ungaria Dualistă: Strategiile de carieră şi reţelele personale ale lui Alexa David la începutul secolului al XX-lea. Studiul de faţă se concentrează asupra traseului educaţional şi profesional al lui Alexa David, unul dintre absolvenţii de drept din ţinutul Năsăudului, în ultima decadă a secolului al XIX-lea şi începutul secolului XX. Experienţele lui David exemplifică una dintre strategiile de construcţie naţională utilizate în regiune, care ţintea constituirea unui corp de indivizi educaţi în domeniul juridic, care puteau să apere interesele naţiunii române în tribunalele maghiare, şi care să contribuie la dezvoltarea sa în toate domeniile. În acelaşi timp, datorită legăturilor de rudenie cu cel mai înalt eşalon politic al Ungariei Dualiste, prin unchiul său Ion Ciocan, deputat în Parlamentul de la Budapesta, tânărul jurist s-a văzut plasat într-o poziţie privilegiată din punct de vedere financiar, fiind de asemenea introdus într-o reţea vastă, întinsă pe multiple comitate, şi cuprinzând indivizi din diferite categorii sociale şi profesionale. A reuşit să se folosească de această reţea în eforturile sale de avansare, returnând ajutorul primit după ce a reuşit să se erijeze ca parte a sistemului administrative al statului maghiar, şi apoi al celui român. Cuvinte-cheie: Austro-Ungaria, Transilvania, studenţi la drept, jurişti, secolul XIX, strategii matrimoniale.